2002
DOI: 10.1074/jbc.m208223200
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Different Modes of Action of the Anticoagulant Protease Inhibitors DX-9065a and Argatroban

Abstract: The accompanying paper (Nagashima, H. (2002) J. Biol. Chem. 277, 50439 -50444) has demonstrated that argatroban can yield a stronger inhibitory effect on thrombin generation than DX-9065a during extrinsic pathway-stimulated human plasma coagulation, while these anticoagulant compounds have comparable abilities to prolong clot time. Since thrombin generation is known to be an important determinant for fibrinolytic resistance of clots formed during coagulation, the two compounds are compared by tissue plasminoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…hirudin and DX-9065a, display little or no profibrinolytic activity. 11,12 Moreover, the enhanced thrombin generation induced by factor VIIa or by tissue factor (TF) has virtually no effect on the fibrinolysis rate, at least under certain conditions. 8,13,14 This highlights the complexity of the interplay between coagulation and fibrinolysis and suggests that the up-and down-regulation of coagulation will be translated into fibrinolytic changes on condition that specific requirements are fulfilled, among which the intensity and timing (in relation to fibrin formation) of thrombin generation play a major role.…”
Section: Introductionmentioning
confidence: 99%
“…hirudin and DX-9065a, display little or no profibrinolytic activity. 11,12 Moreover, the enhanced thrombin generation induced by factor VIIa or by tissue factor (TF) has virtually no effect on the fibrinolysis rate, at least under certain conditions. 8,13,14 This highlights the complexity of the interplay between coagulation and fibrinolysis and suggests that the up-and down-regulation of coagulation will be translated into fibrinolytic changes on condition that specific requirements are fulfilled, among which the intensity and timing (in relation to fibrin formation) of thrombin generation play a major role.…”
Section: Introductionmentioning
confidence: 99%
“…[58]. The results demonstrated that argatroban was more effective than DX-9065a in reducing endogenous thrombin potential (area under thrombin generation curve), especially when coagulation was activated by high TF concentrations.…”
Section: Drug Design and Therapeutic Strategy Planningmentioning
confidence: 73%
“…It is remarkable that models initially developed for basic research [17] have been successfully applied to resolution of practical problems [57,58].…”
Section: Drug Design and Therapeutic Strategy Planningmentioning
confidence: 99%
“…A Monte-Carlo simulation approach for the analysis of this model has been proposed in the paper from Diamond laboratory, which can be found in this issue [48] . The original model of Jones and Mann [46] was also used by other groups for clinical applications to analyze the mechanism of action of synthetic protease inhibitors [49,50] . Finally, the recent study of thrombin generation in reconstituted systems simulated coagulation at different lipid concentrations [51] (previous works assumed saturating phospholipids).…”
Section: Models Of Thrombin Generation Assay and Clot Time Testsmentioning
confidence: 99%